Partner–Child Relationship Satisfaction and Marital Satisfaction: Do Impressions Spill Over? - Kincaid, Reilly (My University, 2021)
Whereas childcare responsibilities are temporary, relationships with children are lifelong. This study examines how parents’ satisfaction with their partners’ relationships with offspring (i.e., “partner–child relationship satisfaction”) influences marital satisfaction, how this compares to the influence of satisfaction with the division of childcare, and how these processes work differently by gender. The author theorizes that partner–child relationship satisfaction shapes marital satisfaction through “impression spillover,” whereby one’s feelings about a relationship between other individuals transfer into feelings about one’s own relationship with one of those individuals. Hypotheses are tested with fixed effects regression using matched-partner data from four waves of the HILDA Survey (N=3804 person-years). Findings suggest that partner–child relationship satisfaction is associated with marital satisfaction, especially among women. Women’s marital satisfaction is influenced more by partner–child relationship satisfaction than by division of childcare satisfaction; conversely, for men, there is little distinction between the two associations. Findings offer support for impression spillover.
Journal of Family Issues
Keywords: Families and relationships